Comparison of Time Utilization of Urban, Rural and Tribal Farmwomen in Farming and Post-Harvest Activities - Bellurkar, Chitra M. (IJRDO - Journal of Applied Management Science, 2017)
Farm women constitute so significant part of working women population in our country that it necessitates a fuller understanding of their status and role not only as they now are but as they may be in future. The study was carried out from two agro–climatic zones of Maharashtra. Nanded district was selected from Central Maharashtra Plateau zone and Nagpur district was selected from Central Vidarbha zone. This research consist sample of 409 farmwomen for farming activities and 410 farmwomen for post-harvest activities from urban, rural and tribal areas. In the present study, time spending pattern of the respondents was compared in farming and post-harvest activities for rabi and kharif seasons. Time spending of the respondents in both the seasons was recorded in days per year. Overall it can be concluded that tribal respondents under this study utilized more time i.e. 126.67 days per year for performing the farming activities followed by rural women who spent 123.05 days. Urban women spent comparatively less time i.e. 104.06 days for farming activities. For the post-harvest activities, urban women spent 77.93 days per year whereas tribal women spent 47.82 days followed by rural women who spent 46.37 days for both the seasons per year.